Dinámica de uso de suelo y sitios prioritarios para la restauración forestal del Corredor Biológico Río Tibás, Costa Rica - Calvo-Villalobos, Jossy Esteban (2019)
An evaluation was conducted on landscape elements (land use, access roads, slopes, and environmental fragility) and trends in the use of soil during the period 2005-2016 in the area proposed for the Biological Corridor Tibas River (CBRT). From these elements and trends, a methodology for the selection of priority sites (SP) was applied for the restoration of plant cover, and a survey to assess the perception and consent of their respective owners was applied. The CBRT has a distribution almost equitable between urban, agricultural and natural use, with an important concentration of forest cover in its high area. However, in 11 years the CBRT has undergone a process of urbanization, up to three times faster than other urban areas in the region, being the agricultural uses the most vulnerable to change. The implementation of the methodology identified 20 priority sites of management; the above-mentioned survey was applied in 10 of them. The 94% of the owners are willing to the restoration, motivated primarily by the conservation of water, biodiversity and landscape.